Cutis 2020
DOI: 10.12788/cutis.0025
|View full text |Cite
|
Sign up to set email alerts
|

Laser Safety: The Need for Protocols

Abstract: Lasers are being used in ever-expanding roles in dermatology. As our understanding of laser energy grew, the need for safety guidelines became apparent. The US Food and Drug Administration (FDA) published the first safety guidelines in 1984, which are updated on a regular basis. However, these are just guidelines, and their implementation is voluntary by the laser practitioner. In this article, we discuss the 4 regulatory entities for laser safety in the United States, laser principles in general, ocular hazar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 12 publications
(29 reference statements)
0
11
0
Order By: Relevance
“…Despite knowledge of the dangerous components of surgical smoke and evidence-based practices to control surgical smoke, healthcare professionals continue to be exposed to surgical smoke [3]. Surgical smoke is a major problem that needs to be addressed and resolved by health professionals due to its negative effects on the respiratory and cardiovascular system, irritating the ocular and mucosal areas, and mutagenic effects [12,13]. It is critical to determine the possible damages of surgical smoke during the operation and to minimize these damages [14].…”
Section: Resultsmentioning
confidence: 99%
“…Despite knowledge of the dangerous components of surgical smoke and evidence-based practices to control surgical smoke, healthcare professionals continue to be exposed to surgical smoke [3]. Surgical smoke is a major problem that needs to be addressed and resolved by health professionals due to its negative effects on the respiratory and cardiovascular system, irritating the ocular and mucosal areas, and mutagenic effects [12,13]. It is critical to determine the possible damages of surgical smoke during the operation and to minimize these damages [14].…”
Section: Resultsmentioning
confidence: 99%
“…There were 4 cases of ocular injury, reiterating the importance of proper eye protection and implementation of laser checklists. 4,23…”
Section: Resultsmentioning
confidence: 99%
“…There were 4 cases of ocular injury, reiterating the importance of proper eye protection and implementation of laser checklists. 4,23 Various specialists were named in laser lawsuits, raising concern regarding appropriate training and scope of practice. 4,6 Physicians without specific training in medical laser devices are held to the same standard of care expected of well-trained physicians.…”
Section: Protecting Yourselfmentioning
confidence: 99%
“…Lasers are currently the dominant light sources for photobiomodulation. Until recently, lasers were thought to exert biologically beneficial effects; however, recent studies have suggested otherwise ( 34 , 35 ). The major difference between lasers and LEDs is the bandwidth.…”
Section: Discussionmentioning
confidence: 99%